2015
DOI: 10.1002/2015wr017595
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Integrated Control of water quality and quantity in urban water reservoirs

Abstract: This paper contributes a novel High‐Performance Integrated Control framework to support the real‐time operation of urban water supply storages affected by water quality problems. We use a 3‐D, high‐fidelity simulation model to predict the main water quality dynamics and inform a real‐time controller based on Model Predictive Control. The integration of the simulation model into the control scheme is performed by a model reduction process that identifies a low‐order, dynamic emulator running 4 orders of magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Zhao et al adopted a decentralized control model in the joint operation of water quality and quantity, and a water quality and quantity feedback mechanism was added in this model in order to give full play of the directive function of water quality simulation results [95]. A high-performance integrated control framework was proposed by Galelli et al to support the real-time operation of urban water supply storages affected by water quality problems, and Delft3D-FLOW was used to simulate nonsteady flow and transport phenomena in Marina Reservoir [96]. To sum up, researches on the joint operation of water quality and quantity pay more attention to the river basin, while research in the urban water supply systems are still lacking.…”
Section: Joint Operation Of Water Quality and Quantitymentioning
confidence: 99%
“…Zhao et al adopted a decentralized control model in the joint operation of water quality and quantity, and a water quality and quantity feedback mechanism was added in this model in order to give full play of the directive function of water quality simulation results [95]. A high-performance integrated control framework was proposed by Galelli et al to support the real-time operation of urban water supply storages affected by water quality problems, and Delft3D-FLOW was used to simulate nonsteady flow and transport phenomena in Marina Reservoir [96]. To sum up, researches on the joint operation of water quality and quantity pay more attention to the river basin, while research in the urban water supply systems are still lacking.…”
Section: Joint Operation Of Water Quality and Quantitymentioning
confidence: 99%
“…Water Resources Research RESEARCH ARTICLE model predictive control (Anghileri et al, 2016;Galelli et al, 2015;Mayne et al, 2000;Raso & Malaterre, 2017). Other studies (Cai et al, 2002;Shiau, 2011) used nonlinear optimization formulations with constrained carryover storage volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Most approaches for efficient allocation of reservoir storage are limited by the so‐called curse of dimensionality where computational time and memory to increase exponentially with the number of storage units (Bellman & Dreyfus, ; Giuliani et al, ). Examples include dynamic programming (Banihabib et al, ; Fontane & Labadie, ; Ji et al, ; Mansouri et al, ; Marino & Mohammadi, ; Tauxe et al, ; Yakowitz, ; Yeh & Becker, ), stochastic dynamic programming (Butcher, ; Scarcelli et al, ; Soleimani et al, ; Stedinger et al, ; Torabi & Mobasheri, ; Zhou et al, ), and model predictive control (Anghileri et al, ; Galelli et al, ; Mayne et al, ; Raso & Malaterre, ). Other studies (Cai et al, ; Shiau, ) used nonlinear optimization formulations with constrained carryover storage volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Surrogate modelling is an approach to develop a simpler and faster model emulating the outputs of a more complex simulator as a function of its inputs and parameters [1]. Surrogate models are useful when the simulators are computationally expensive for applications such as model-based real time control (RTC) [2], model calibration [3], design optimization [4], Monte Carlo based uncertainty propagation analysis [5], or sensitivity analysis [6]. In Urban Drainage Modelling (UDM), most of the urban drainage simulators are also among the computationally demanding modelling tools.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards this process is conditioned on certain selected design data to produce a posterior, which is called the emulator [3]. To date, several studies have confirmed the effectiveness of application of the emulators in acceleration of hydrological and hydrodynamic simulators for purposes such as uncertainty propagation analysis using the Monte Carlo method [5]; optimal dam operation [23,24]; and Real-time Model Predictive Control (RT-MPC) [2].…”
Section: Introductionmentioning
confidence: 99%